Model of Controlling System for Religious Programs in Public Schools: A Case Study at SMA Negeri 1 Rambutan Banyuasin - Juanda Firzal; Asri Karolina; Afriantoni Afriantoni; Yuniar Yuniar (Journal of Educational Sciences, 2026)
This study examines the controlling system of religious programs in public schools through a case study at SMA Negeri 1 Rambutan Banyuasin. As a public educational institution, the school is responsible for fostering students’ religious values, character, and moral development alongside academic achievement. The research employed a qualitative phenomenological approach with a case study design. Data were collected through observations, in-depth interviews, and documentation involving the principal, vice principal, head of the religious program, and Islamic education teachers. The findings reveal that religious activities are implemented systematically through daily, weekly, monthly, and incidental programs, including collective prayers, congregational Dhuhr and Dhuha prayers, Qur’an recitation, Rohis mentoring, Friday religious discussions, and Islamic holiday commemorations. These activities encourage students to develop religious habits, discipline, responsibility, tolerance, and social awareness. The controlling system is carried out through integrated planning, coordination among school personnel, routine monitoring, periodic evaluation, stakeholder involvement, teacher role modeling, and continuous reflection to improve program quality. Although the implementation faces challenges such as limited human resources, inconsistent monitoring, and the lack of digitalized supervision, the overall system effectively supports students’ spiritual and character development. The study proposes a school-based religious governance model that can serve as a practical reference for other public schools seeking to strengthen character education through structured and sustainable religious programs.